Pharmacological perspectives from Brazilian Salvia officinalis (Lamiaceae): antioxidant, and antitumor in mammalian cells - GARCIA,CHARLENE S.C. (2016)
ABSTRACT Salvia officinalis (Lamiaceae) has been used in south of Brazil as a diary homemade, in food condiment and tea-beverage used for the treatment of several disorders. The objective of this study was to characterize chemical compounds in the hydroalcoholic (ExtHS) and aqueous (ExtAS) extract from Salvia officinalis (L.) by gas chromatography-mass spectrometry (GC-MS) and by high-resolution electrospray ionization mass spectrometry (ESI-QTOF MS/MS), evaluate in vitro ability to scavenge the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH•) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+), catalase (CAT-like) and superoxide dismutase (SOD-like) activity, moreover cytotoxic by MTT assay, alterations on cell morphology by giemsa and apoptotic-induced mechanism for annexin V/propidium iodide. Chemical identification sage extracts revealed the presence of acids and phenolic compounds. In vitro antioxidant analysis for both extracts indicated promising activities. The cytotoxic assays using tumor (Hep-2, HeLa, A-549, HT-29 and A-375) and in non-tumor (HEK-293 and MRC-5), showed selectivity for tumor cell lines. Immunocytochemistry presenting a majority of tumor cells at late stages of the apoptotic process and necrosis. Given the results presented here, Brazilian Salvia officinalis (L.) used as condiment and tea, may protect the body against some disease, in particularly those where oxidative stress is involved, like neurodegenerative disorders, inflammation and cancer.